Reactive Oxygen Species Generation in Human Cells by a Novel Magnetic Resonance Imaging Contrast Agent. (26th March 2018) - Wang, Li; Lin, Eric; Johansen, Mary J.; Madden, Timothy; Felix, Edward; Martirosyan, Karen S.; Frank, Steven J.
Abstract : The novel positive-contrast magnetic resonance imaging (MRI) marker C4 consists of an aqueous solution of cobalt chloride (CoCl2 ) complexed with the chelator N-acetylcysteine (NAC). We evaluated whether the presence of C4 or its components would produce reactive oxygen species (ROS, including hydroxyl, peroxyl, or other reactive oxygen species) in cultured cells. Human cancer or normal cells were incubated with 1% (w/v) CoCl2 ·6H2 O or 2% NAC or a combination of both (1% CoCl2 ·6H2 O : 2% NAC in an aqueous solution, abbreviated as Co : NAC) in the presence or absence of H2 O2 . Intracellular ROS levels were measured and quantified by change in relative fluorescence units. Student'st -tests were used. In all cell lines exposed to 1000 μ M H2 O2, the Co : NAC led to ≥94.7% suppression of ROS at 5 minutes and completely suppressed ROS at 60 and 90 minutes; NAC suppressed ROS by ≥76.6% at 5 minutes and by ≥94.5% at 90 minutes; and CoCl2 ·6H2 O suppressed ROS by ≥37.2% at 30 minutes and by ≥48.6% at 90 minutes. These results demonstrate that neither Co : NAC nor its components generated ROS; rather, they suppressed ROS production in cultured cells, suggesting that C4 would not enhance ROS production in clinical use.